The Small Giant Clam, Tridacna maxima Exhibits Minimal Population Genetic Structure in the Red Sea and Genetic Differentiation From the Gulf of Aden - Lim, Kah Kheng; Rossbach, Susann; Geraldi, Nathan R.; Schmidt-Roach, Sebastian; Serrão, Ester A.; Duarte, Carlos M. (Frontiers in Marine Science, 2020)
The Red Sea serves as a natural laboratory to investigate mechanisms of genetic differentiation and population dynamics of reef organisms due to its high species endemism. Giant clams, important yet understudied coral reef engineering species, are ideal candidates for such study in this region. This paper presents the first population genetics study of giant clams covering the entire East coast of the Red Sea. Our study aimed to investigate the population structure of the small giant clam, Tridacna maxima, based on 501-bp fragment of the cytochrome c oxidase I gene from 194 individuals (126 new sequences from this study plus 68 sequences from GenBank), collected from 14 locations in the Red Sea and Gulf of Aden (RSGA). For the genetic analysis, each sampling site was treated as a population. T. maxima showed high genetic diversity, with high gene flow in almost all sampling sites. The insignificant global ϕST-value of 0.02 (p > 0.05) suggests the presence of one large, panmictic population across a wide range of temperature and salinity gradients in the RSGA. Despite this, the population in Djibouti was genetically differentiated from the other 11 populations in the Red Sea, suggesting a connectivity break between the Red Sea and the Gulf of Aden. These results could be explained by the oceanographic features facilitating wide larval transport inside the Red Sea, and creating a dispersal barrier to the Gulf of Aden. Besides larval dispersal by currents, apparent successful establishment following dispersal is probably facilitated by the mode and time of reproduction as well as the ability of T. maxima to achieve high fitness in the highly variable environmental conditions of the Red Sea.